Hygroscopicity Categorization of Pharmaceutical Solids by Gravimetric Sorption Analysis: A Systematic Approach - Allada, Ravikiran (Asian Journal of Pharmaceutics (AJP), 2016)
Context: Hygroscopicity is the ability of a material to absorb or adsorb moisture from surrounding environment. Hygroscopicity of pharmaceutical solids is often evaluated due to the fact that the up-taken moisture can impact physical and chemical stability of the pharmaceutical products. In pharmaceutical industry, the most commonly used conventional method for hygroscopicity is as per the European Pharmacopeia (Ph. Eur.). The Ph. Eur. method relies on equilibrium for 24 h at 25°C – 80% relative humidity and it does not take the initial moisture content of the material into consideration, but the initial moisture content is critical in interpreting the hygroscopicity of any material. Aim: In this current work, we emphasize the necessity of sample pretreatment, by which the sample achieves a dry reference initial state, which plays an important role in deriving calculations required for accurate interpretation, and thereby right hygroscopicity categorization. Materials and Methods: The proof-of-concept experiments were performed on seven pharmaceutical solids (four antihypertensive drugs and three commonly used excipients). The studies are conducted using gravimetric sorption analyzer, an instrument, which is capable of controlling humidity and measuring weights accurately. Each of the pharmaceutical solid was subjected to the pretreatment followed by equilibrating at 25°C – 80% RH. Separately, the seven pharmaceutical solids were evaluated using conventional Ph. Eur. Method, and the results from both approaches are compared. Results: The results show that the proposed method not only enables higher throughput but also gives a more accurate interpretation when compared with that of Ph. Eur. method. Conclusion: Finally, we present a systematic approach to examine samples to establish the right hygroscopicity categorization of pharmaceutical solids.